การศึกษาต้นทุนการบำบัดฟื้นฟูผู้ต้องขังคดียาเสพติดในทัณฑสถานบำบัดพิเศษหญิง อ.ธัญบุรี จ. ปทุมธานี - จิราพร ตันติหาชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this retrospective descriptive study was to explore unit cost of drug offenders rehabilitation and unit cost of projects in women correctional institution for drug addicts. Data were collected on October 1,2005- September 30, 2006. The instruments for collecting data were cost collecting forms. The data were analyzed by using Microsoft exel 2000. The study results showed that there were 1,667 drug offenders in women Correctional Institution for Drug Addicts. Total length of stay in prison was 461,063 days. Full cost was 24,796,153 bath per year. Unit cost were 14,874.72 bath per inmate or 53.78 bath per day. Unit cost of activities such as Cookery training was 656.36 bath per inmate, Chorus project for drug offenders was 645.53 bath per inmate, Cloth painting activity was 482.02 bath per inmate, Papermache training was 476.40 bath per inmate, English training program 5 th was 346.64 bath per inmate, Exercise activity was 287.26 bath per inmate, English training program 6 th was 274.98 bath per inmate, Re - entry program was 256.44 bath per inmate, Family relation activity was 88.53 bath per inmate, Community therapeutic program was 18.14 bath per inmate and meditation practice project was 13.52 bath per inmate. The findings will be primary information to set the policies and administer organization in order to use the limited resource for the most benefit. In addition, its results are useful inputs for more appropriate decision making about budget planning.